IMPLEMENTASI KEBIJAKAN PENYELENGGARAAN REKLAME DI KOTA SEMARANG - Niandanu, Panji Yudha; Suryaningsih, Margaretha; Rihandoyo, Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Increased competition in trade and the development of urban areas which is very fast, spurred the emergence of private sign namely commercial messages in the form of ads. Ads it can be said is a means of potent for the promotion of all kinds of good business information, politic, as well as social activities designed the government. Nowadays, the government the city of Semarang still had difficulty in an effort to control growth ads. Many establishment point of billboard irresponsible so very disturbing views , even the safety of road users. Hence, formulated by law the City of Semarang No.14 2012 about the ads. The purpose of this research is to find and analyze of policy implementation of advertising in semarang city and to know and identifies factors success of policy implementation of advertising within the city of semarang. The theory used among others the theory of public administration , public policy, and the implementation of policy. A subject in this research is 5 people, where 3 people from dept. of associated with ads implementation and 2 people from businessmen bureau ads. Type research used is a type descriptive with the approach research methodology qualitative. While techniqued data collection was carried out by interviews and the literature study. Analysis data was undertaken to technique the data, reduction data, presentation of and the withdrawal of conclusion / verification. The results of the study showed that implementation of advertising of policy within the city of Semarang been entirely successful. This is because available resources also it is not enough, even you could say very weak to carry out of policy implementation of advertising. In addition, absence of a close coordination meeting who do not routinely done and also enforcement in the field are single own and rarely coordinate between the dept. of associated with ads implementation also related been to cause that has not been of policy the ads within the city of Semarang.